PLANTING PATTERN AND IRRIGATION EFFECT ON FARMLAND MICROCLIMATE AND YIELD OF WINTER WHEAT - X. Y. Wang; Z. Zhang; X. B. Zhou; P. Liu; Y. H. Chen (Journal of Animal and Plant Sciences, 2015)
The use of water resources should be restricted until a suitable irrigation and planting system is developed in the North China Plain. This study was aimed to study the effects of planting pattern and irrigation on the farmland microclimate, and indentify possible ways to improve the yield of winter wheat. The field experiments in a randomized complete block design with four replicates were conducted during the 2008-09 and 2009-10 growing seasons in Taian, China. The three planting patterns were: 25 cm uniform row planting pattern (U), “20 + 40” wide-narrow row planting pattern (WN), and “20 + 40” furrow planting pattern (F). Three irrigation treatments applied: were 90, 135, and 180 mm during the whole growth period. Results showed that F had 3.5% lower diurnal soil temperature at the 5cm soil depth, 4.7% lower diurnal air temperature at 5cm above the ground, 14.8% lower diurnal relative humidity (RH), 4.8% higher soil water content (SWC) at the 0 cm to 30 cm soil depth, and 9.7% higher yield as compared with U. Irrigation decreased soil temperature and air temperature but increased RH and SWC. The yield of 135 mm irrigation was 6.4% higher than that of 90 mm. The grain yield of winter wheat was not significantly difference between 135 and 180 mm irrigation from 2009-10 (P > 0.05). Therefore, F and 135 mm irrigation were regarded the best combination as the optimum conditions for winter wheat considering the water shortage problem in China.
Keywords: soil temperature; air temperature; relative humidity; soil water content